Examining the Influence of Locus of Control and Perceived Behavior Control on Fraud Prevention with Whistleblowing as an Intermediate Variable: A Case Study of PT. Lintang Kejora Semarang - Andika, Arditya Dian; Martadi, Nana Storada Dwi; Paramita, Patricia Dhiana; Ratnawati, Juli (Universitas Dian Nuswantoro Semarang, 2024)
This study investigates the intricate relationship between locus of control, perceived behavior control, and fraud prevention, with whistleblowing as a mediating construct. The research adopted a comprehensive sampling strategy known as a census approach, which encompassed the entirety of the employee population at PT. Lintang Kejora, comprising a total of 100 individuals, thereby ensuring their inclusion as research respondents. The data analysis methodologies employed in this study comprised two-stage least-squares regression and path analysis. The results of the data analysis indicate that locus of control and perceived behavior control exert a partially positive and statistically significant influence on whistleblowing. However, locus of control and perceived behavior control do not appear to have a significant impact on fraud prevention. Additionally, whistleblowing exhibits a positive and statistically significant influence on fraud prevention. Nevertheless, whistleblowing does not mediate the impact of locus of control and perceived behavior control on fraud prevention to a significant extent. These findings shed light on the multifaceted interplay between individual psychological attributes, whistleblowing, and fraud prevention within organizations. Addressing these implications can aid in the development of more effective strategies for preventing and managing fraud in organizational settings. Keywords:locus of control, perceived behavior control, personal cost, whistleblowing, fraud prevention